Management of Community Forests in Tamil Nadu - Wilson, J. (Indian Forester, 1986)
The State of Tamil Nadu stands in the fore front in the establishment of community forests in the country. The revenue obtained from the sale proceeds of these forests are being shared with the village panchayats. The panchayats in turn have utilised these revenues for various aspects of rural development. Studies made have, however, revealed that although the community has been greatly benefited by payment of 50 per cent share of the sale proceeds, most of the fuelwood generated in these forests finds its way to urban channels mainly because there is no real fuel scarcity in rural Tamil Nadu. In order to channelise the assets generated in the community forests to meet the rural requirements of the people, a reorientation of the management practices presently followed is necessary. The present rotation of 10 years designed mainly for the production of fuelwood needs to be given up for a longer rotation in order to produce small timber and increased grazing facilites over a longer period for the rural community. Several experimental models have been implemented during the last two years in order to standardise harvesting of these plantations with the involvement and participation of the rural people. Pruning of lower branches are carried out In all three Village tank years Social bed plantat ions over of age through the Forestry Committees and the pruned material is distributed to the villagers for use as fuel. The need for organising sheep co-operatives to enable th’e weaker sections in the village to take advantage of the improved grazing facilities and the ’pods produced in abundance is under serious consideration. Likewise, the collection of other produce generated in these community plantations such as gum Arabic and green leaf manure also needs to be organised by formation of village co-operatives.